The Grassroots and Party Funding in Nigeria: Trajectories for Money Politics - Fadakinte, M. M.; Nwali, Uche (Advances in Social Sciences Research Journal, 2021)
This paper addresses grassroots indifference to party funding in Nigeria. It argues that all existing explanations on political apathy do not address the escalating tendency of the ordinary but educated and politically aware Nigerians to be averse to party funding. Drawing on political culture theory, the paper attributes the current trajectory of the phenomenon to a form of "inverse participant" culture by the grassroots, consequent upon their alienation that is driven by a convergence of three key variables: the cartel nature of party formation which is responsible for the disconnect in state-society relations, the appropriation and weaponisation of parties through funding, and decades of unfulfilled campaign promises. It further contends that grassroots indifference creates a funding vacuum which gives room for the monopoly of the party by the wealthy few and the moneybags. The paper concludes that, to arrest grassroots disinterest in party funding, it will require a reform of the Nigerian state to wean it of predatory and exclusionary character and arrest the prevailing cartelization of party formation and appropriation of political parties. It is also important to evolve a political culture that will create positive civic consciousness so as to shape voter-party-candidates relations in order to arrest the current negative voter attitudes that expect and demand for money from party candidates. This paper adopted the qualitative method of research , making use of extant literature on the subject matter and in addition used the interview method in seeking the opinions of a few individuals, some of them party card carrying members.